Experimental Analysis of Red Gram Stalk Pellet Non-Conventional Energy Potential from Agricultural Residue Biomass as an Alternate Fuel for Internal Combustion Engines: Exploring the Potential of Red Gram Stalk Pellet Biomass as an Alternative Fuel (Journal of Advances and Scholarly Researches in Allied Education, 2020)
As one of the many renewable energy sources, producer gas presents a great prospect for long-term energy and transportation sector sustainability. In locations where petroleum and diesel costs are high or supply are inconsistent, producer gas can provide an economically feasible option. The Red Gram stalk pellet producer gas composition is detailed in this study. The calorific value of Red Gram stalk biomass is also discussed in this paper. The study was undertaken to investigate the properties of Red Gram stalk fuel from the agricultural residues. The ultimate analysis of the Red Gram stalk on air dried basis in terms moisture content 5.9 , ash content 1.85 , fixed carbon 42.57 , hydrogen 5.71 , nitrogen 0.41 , sulphur 0.35 , oxygen 43.21 and calorific value of Red Gram stalk biomass is 14820 KJKg respectively.